2015
DOI: 10.1142/s0192415x15500925
|View full text |Cite
|
Sign up to set email alerts
|

Potential Wound Healing Activities of Galla Rhois in Human Fibroblasts and Keratinocytes

Abstract: Wound healing is a complex process orchestrated by the regeneration of the epithelium and the remodeling of the extracellular matrix through processes like collagen deposition. Galla Rhois has been widely used in traditional Korean medicine for its various pharmacological effects, including an anticoccidial effect, however, little is known about its healing activity. The purpose of this study was to determine the effects of Galla Rhois ethanol extract (GRE) on wound healing activities, including H2O2-induced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Normally, for the damage of the external environment, skin can protect the integrity and function of internal organs very effectively (22,32). Therefore, in the process of resisting environmental stimuli, the skin will be damaged to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, for the damage of the external environment, skin can protect the integrity and function of internal organs very effectively (22,32). Therefore, in the process of resisting environmental stimuli, the skin will be damaged to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate levels of ROS are beneficial for wound repair. However, excessive ROS production leads to oxidative stress, and inhibits the proliferation and migration of cells in wound repair (21,22). In addition, high levels of oxidative stress prolong the inflammatory process, induce tissue damage and results in the delay of wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…In general, skin is regarded as a barrier to protect the inner organs from environmental damage, which makes it extremely vulnerable to different types of lesions [30]. Skin wounds can cause the inner organ to become ill with poor nutrition and even death [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HSF also played an important role in wound healing. 26,27 We therefore experimentally tested whether exosomal miR-19b could have an effect on HSF. We first confirmed that exosomes could be taken up by HSF, and we observed a significant uptake of exosomes by HSF after 48 hours of incubation with exosomes ( Figure 6A).…”
Section: Exosomal Mir-19b Contributes To the Proliferation And Migratmentioning
confidence: 99%